2019
DOI: 10.1021/acsami.8b22370
|View full text |Cite
|
Sign up to set email alerts
|

Rational Surface Tailoring Oxygen Functional Groups on Carbon Spheres for Capacitive Mechanistic Study

Abstract: Porous carbons represent a typical class of electrode materials for electric double-layer capacitors. However, less attention has been focused on the study of the capacitive mechanism of electrochemically active surface oxygen groups rooted in porous carbons. Herein, the degree and variety of oxygen surface groups of HNO3-modified samples (N-CS) are finely tailored by a mild hydrothermal oxidation (0.0–3.0 mol L–1), while the micro–meso–macroporous structures are efficiently preserved from the original sample.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 65 publications
0
30
0
Order By: Relevance
“…It can be observed that the signal intensity of the O element increased after treatment, while the signal intensity of the C element was almost unchanged, which can also be verified in the C 1s and O 1s core-level spectra (Figure c,d). From the C 1s spectrum, the peaks at 284.8, 286.0, 287.1, 289.1, and 291.7 eV were obtained after peak deconvolution, revealing the existence of C–C/CC, hydroxyl (C–O), carbonyl (CO), carboxyl (O–CO), and π–π shake-up satellite peak. The percentages of individual carbon-containing functional groups are calculated according to their peak areas (Table S2). To figure out the species of groups that dominate in the increase of O content, the O 1s spectrum was also analyzed.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It can be observed that the signal intensity of the O element increased after treatment, while the signal intensity of the C element was almost unchanged, which can also be verified in the C 1s and O 1s core-level spectra (Figure c,d). From the C 1s spectrum, the peaks at 284.8, 286.0, 287.1, 289.1, and 291.7 eV were obtained after peak deconvolution, revealing the existence of C–C/CC, hydroxyl (C–O), carbonyl (CO), carboxyl (O–CO), and π–π shake-up satellite peak. The percentages of individual carbon-containing functional groups are calculated according to their peak areas (Table S2). To figure out the species of groups that dominate in the increase of O content, the O 1s spectrum was also analyzed.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The C−O stretching vibration corresponds to the peak at 1058 cm −1 , which may indicate the presence of ester, epoxide, ether, and phenol groups. [ 47–49 ] Furthermore, X‐ray photoelectron spectroscopy (XPS) is conducted to further confirm the types of chemical bonds (Figure 1f). Specifically, three fitting peaks can be observed in the high‐resolution O 1 s spectrum, attributed to the CO, OCO, and chemisorbed O, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, an unreasonable increase in the proportion of oxygen functional groups will tightly trap ions and reduce the probability of ion intercalation. 99 Compared with aqueous electrolytes, organic electrolytes provide a broader electrochemical stability window (42 V), which can significantly boost the energy densities of electric double-layer capacitors. 100 At present, the majority of commercial electric double-layer capacitors utilize organic electrolytes.…”
Section: O-doped Porous Carbonsmentioning
confidence: 99%